2007
DOI: 10.1021/bc060306g
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-Labeled Alpha-Melanocyte-Stimulating Hormone Analog for MicroPET Imaging of Melanocortin 1 Receptor Expression

Abstract: The alpha-melanocyte-stimulating hormone (α-MSH) receptor (melanocortin type 1 receptor, or MC1R) plays an important role in the development and growth of melanoma cells. It was found that MC1R was overexpressed on most murine and human melanoma, making it a promising molecular target for melanoma imaging and therapy. Radiolabeled α-MSH peptide and its analogs that can specifically bind with MC1R have been extensively explored for developing novel agents for melanoma detection and radionuclide therapy. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 26 publications
5
109
2
1
Order By: Relevance
“…4). We recently synthesized a 64 Cu-labeled α-MSH peptide, 64 Cu-DOTA-NAPamide, and successfully demonstrated its use for microPET imaging of melanoma and MC1R expression (21,22). In this research, we further develop 18 F-labeled NAPamide as a molecular imaging probe for MC1R microPET imaging.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4). We recently synthesized a 64 Cu-labeled α-MSH peptide, 64 Cu-DOTA-NAPamide, and successfully demonstrated its use for microPET imaging of melanoma and MC1R expression (21,22). In this research, we further develop 18 F-labeled NAPamide as a molecular imaging probe for MC1R microPET imaging.…”
mentioning
confidence: 99%
“…The MC1R is overexpressed in most murine and human melanoma metastases (7,8), thus making it a promising molecular target for imaging and therapy of melanomas. Various α-MSH peptides radiolabeled with 18 F (9), 99m Tc (10,11), 111 In (12)(13)(14)(15)(16)(17), 125 I (18), 67 Ga (19), 86 Y (20), and 64 Cu (20)(21)(22) that can recognize the MC1R in vitro or in vivo have been prepared and evaluated for melanoma detection. Moreover, an α-MSH peptide, ReCCMSH (Arg 11 ), radiolabeled with a therapeutic radionuclide-either 188 Re or 212 Pb-has shown promising therapeutic efficacy in mice bearing either B16F1 murine or TXM13 human xenografted melanoma (23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor to muscle ratio of 68 Ga-DOTA-ReCCMSH(Arg 11 ) (43.2 ± 15.3) is similar to that of 64 Cu-CBTE2A-ReCCMSH(Arg 11 ) (44.6 ± 9.76, p = NS) and is significantly higher compared to 64 Cu-DOTAReCCMSH(Arg 11 ) (18.5 ± 3.17, p < 0.01). The 86 Y-DOTA-ReCCMSH(Arg 11 ) data [40] is superior to that seen for both 64 Cu DOTA-and 64 Cu-CBTE2A-ReCCMSH(Arg 11 ) analogs [40,46] as well as that seen for 67/68 Ga-DOTA-NAPamide [34], 64 Cu-DOTA-NAPamide [32], 18 F-FB-NAPamide [33], 18 F-FDG [40] and 68 Ga-DOTA-ReCCMSH(Arg 11 ). Overall differences in tumor accumulation can be attributed to the amount of peptide mass administered to the animals, differences in tumor types and volumes, and the status of the tumor cells maintained within each laboratory so care must be taken in the comparison of the current studies with those previously reported [32][33][34]40].…”
Section: Discussionmentioning
confidence: 96%
“…There have been a number of reports on α-MSH peptide-based agents that have demonstrated the ability to image the MCR1 receptor in vivo [31][32][33][34][35][36][37][38][39]. We previously described an α-MSHtargeting peptide system, DOTA-ReCCMSH(Arg 11 ), that was labeled with β + -emitting radiometals, as potential agents for the detection of malignant melanoma via PET imaging [40].…”
Section: -[ 18 F]fluoro-2-deoxy-d-glucose ([ 18 F]fdg)mentioning
confidence: 99%